Incidental vocabulary acquisition from listening to English teacher education lectures: A case study from Macau higher education - Reynolds, Barry Lee; Xie, Xiaowen (Serina); Pham, Quy Huynh Phu (Frontiers in Psychology, 2022)
Some proponents of higher education English as a medium of instruction (EMI) have suggested listening to English lectures provides students the opportunity to incidentally acquire unknown words. A case study was designed to examine this assumption. First, the lexical profiles of twenty-seven Introduction to English Language Teaching first-year undergraduate course lectures were computed to determine how many words students need to know for comprehension. Then an incoming year-1 undergraduate student with an English vocabulary size of 7,500 word families and mastery of the most frequent 3,000 word families listened to these lectures across 13.5 weeks with the purpose of measuring incidental acquisition gains of three aspects of word knowledge for ten targeted words. Lastly, the student’s perceptions about listening to EMI lectures and potentials for this listening inducing incidental acquisition of word knowledge were gathered through a semi-structured interview. The lexical profiling of the entire corpus showed students need knowledge of the most frequent 4,000 English word families plus proper nouns and marginal words for 98% lexical coverage; however, some lectures present students with a more substantial lexical burden than the lectures overall. The student made the most gains in receptive meaning, followed by receptive form, and finally productive meaning. Content analysis of the interview transcript found seven themes representing the student’s perception about listening to EMI lectures and their potential for inducing incidental vocabulary acquisition. While the student found listening to the EMI lectures challenging, he perceived the process as useful in preparing for university studies and a career as a secondary English teacher. The student perceived attention, topic, existing vocabulary knowledge, lecturer’s native language, and lack of interaction with the lecturer to have moderated incidental learning of vocabulary through listening to English lectures. These results indicate a need to confirm whether incoming students’ vocabulary knowledge meet the lexical demands of the EMI lectures given in the Macau context. Furthermore, pedagogical training on teacher talk strategies and orientation training for incoming students should both be provided to ensure students are receiving high quality instruction.